2007
DOI: 10.1007/s10344-007-0159-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of wild boar (Sus scrofa) for porcine reproductive and respiratory syndrome in some territories of Russia

Abstract: Samples of blood sera and internal organs were collected from 90 shot wild boars (Sus scrofa) in five regions of Russian Federation. Blood sera were tested for antibodies against porcine reproductive and respiratory syndrome virus (PRRSV) using enzyme-linked immunosorbent assay (ELISA). In addition, samples of internal organs (lungs, lymph nodes, spleen) were tested by polymerase chain reaction (nested PCR) for PRRSV antigen. The result of our investigation showed that all samples were negative. However, PRRSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
1
2
1
Order By: Relevance
“…Surveys of wild boars from eastern Slovakia have revealed that PRRSV was present in 1.6 % of samples when tested by nested RT-PCR [ 31 ], and PRRSV Type 1 was accidentally identified in a road killed wild boar in Italy [ 25 ]. Contrary to our results, Kukushkin et al [ 20 ] failed to detect PRRSV in tissue samples from wild boars in Russia using RT-PCR, while a study in Poland found that PRRSV infections were not prevalent in wild boars [ 32 ]. The sera and tissues from wild boars in south-central Spain were also found to be negative by conventional and real-time RT-PCR assays [ 18 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Surveys of wild boars from eastern Slovakia have revealed that PRRSV was present in 1.6 % of samples when tested by nested RT-PCR [ 31 ], and PRRSV Type 1 was accidentally identified in a road killed wild boar in Italy [ 25 ]. Contrary to our results, Kukushkin et al [ 20 ] failed to detect PRRSV in tissue samples from wild boars in Russia using RT-PCR, while a study in Poland found that PRRSV infections were not prevalent in wild boars [ 32 ]. The sera and tissues from wild boars in south-central Spain were also found to be negative by conventional and real-time RT-PCR assays [ 18 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The seroprevalence of antibodies against PRRSV in wild boars has been determined to range from 0.3 to 3.6 % in several countries [ 12 19 ]; however, in the Campania Region of Italy, a seroprevalence of 37.8 % was detected [ 17 ]. Many other studies have reported negative PRRSV seroprevalence results [ 20 24 ]. PRRSV has also been detected using reverse transcription polymerase chain reaction (RT-PCR) methods in the lung tissue of wild boars in Italy [ 25 ], Germany [ 26 ] and Lithuania [ 27 ] as well as in the lung tissue of hybrid wild boars, known as “special wild pigs” in China [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to same authors, on PPV identification in wild boar populations, the estimated prevalence of PPV genotypes is 69.6% for PPV3, 63.8% for PPV1, and 21.7% for PPV2. There were no positive samples for PRRSV in our investigation, which aligns with the findings of Kukushkin et al [31], who also did not detect PRRSV-positive animals in wild boar populations across five regions in Russia. Considering that we utilized samples of lymph nodes, spleen, and kidney, we cannot entirely rule out the possibility of PRRS presence in the wild boar population in Serbia.…”
Section: Discussionsupporting
confidence: 92%
“…In the USA, no positive samples were detected in the samples collected in 1976 and in 1993, and only two positive animals were found in 1994 by Lutz and Wurm (16). No PRRSV antibodies were found in wild boars in the neighbouring Poland and Russian Federation (10,14). Blood serum investigations of boars were negative in Switzerland, Spain, Croatia and Slovenia (7,21,27,28,30).…”
Section: Discussionmentioning
confidence: 99%